PERCEIVED HUMAN RESOURCE PRACTICES DURING COVID-19 PANDEMIC: A STUDY AMONG TOUR GUIDES IN KOTA KINABALU, MALAYSIA - Datu Razali Datu Eranza; Shanan Navindra Shan Pillai; Andy Lee Chen Hiung; Jabil Mapjabil; Siti Hasnah Tanalol; Arsiah Bahron (International Journal of Accounting, Finance and Business, 2021)
COVID-19 has plunged global economy to recession and impacted businesses in allsectors, with reduction of manpower and termination of employment. Business organizations,especially those in the tourism industry may need to consider to continuously providingcreative and innovative ways to support tour guides for personal development and selfenrichment.Support system like cost-effective training programme to tour guides can bemeaningful and gain the affective commitment among the tour guides even post-termination.New approach in compensation, training and development, and performance appraisal wouldlead to a preparation for job performance in the future. The study has sampled 279 tour guidesin Kota Kinabalu City, Sabah using online questionnaire, consists of questions related tohuman resource practices. The results suggested that all the practices studied have significantrelationship to employee job performance especially during the difficult time of COVID-19pandemic. The study recommends business firms to design an innovative and creative HRpractices to support the tour guides regardless of the status of being employed or have beenterminated. This may include facilitation of online training provided (free) by agencies anduniversities around the globe, financial aid and assistance programme by the Government, andfacilitation of vaccination programme that could be very much meaningful to the tour guides.